Linking families and facilities for care at birth: What works to avert intrapartum-related deaths? - Lee, Anne CC (2009)
BACKGROUND: Delays in receiving effective care during labor and at birth may be fatal for the mother and fetus, contributing to 2 million annual intrapartum stillbirths and intrapartum-related neonatal deaths each year. OBJECTIVE: We present a systematic review of strategies to link families and facilities, including community mobilization, financial incentives, emergency referral and transport systems, prenatal risk screening, and maternity waiting homes. RESULTS: There is moderate quality evidence that community mobilization with high levels of community engagement can increase institutional births and significantly reduce perinatal and early neonatal mortality. Meta-analysis showed a doubling of skilled birth attendance and a 35% reduction in early neonatal mortality. However, no data are available on intrapartum-specific outcomes. Evidence is limited, but promising, that financial incentive schemes and community referral/transport systems may increase rates of skilled birth attendance and emergency obstetric care utilization; however, impact on mortality is unknown. Current evidence for maternity waiting homes and risk screening is low quality. CONCLUSIONS: Empowering communities is an important strategy to reduce the large burden of intrapartum complications. Innovations are needed to bring the poor closer to obstetric care, such as financial incentives and cell phone technology. New questions need to be asked of “old” strategies such as risk screening and maternity waiting homes. The effect of all of these strategies on maternal and perinatal mortality, particularly intrapartum-related outcomes, requires further evaluation.